ANALISIS PERBEDAAN RATA-RATA PENJUALAN MOBIL DI BALI BERDASARKAN MEREK DAN KUALITAS PRODUK (Studi Kasus pada 5 merek mobil : Toyota, Suzuki, Daihatsu, Honda dan Mitsubishi ) - Kadek Jemmy Waciko (Soshum: Jurnal Sosial dan Humaniora, 2014)
This study aims to determine the difference in average of cars selling in Bali based on brand and quality products of the five car brands: Toyota, Suzuki, Daihatzu, Honda and Mitsubishi. The method used in this study is a Two Way ANOVA. The Results achieved in this study that trademark significantly influence brand difference in the average of car selling are compared, while the quality of the product does not significantly affect the average difference in sales.